2014
DOI: 10.1039/c4dt00899e
|View full text |Cite
|
Sign up to set email alerts
|

Eu@COK-16, a host sensitized, hybrid luminescent metal–organic framework

Abstract: A new concept of luminescent host-guest materials was developed by introduction of Eu(3+) into COK-16, a HKUST-1 type hybrid metal-organic framework (MOF) with cation exchange properties. In Eu@COK-16, the luminescent ion resides in the pore system of the MOF. The luminescence properties of Eu@COK-16 have been studied based on excitation and emission, allowing analysis of intramolecular energy-transfer processes from the COK-16 host to the exchanged Eu(3+) ions. Both the framework trimesate (BTC) and encapsula… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
11
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(12 citation statements)
references
References 27 publications
1
11
0
Order By: Relevance
“…This indicated that the number of sites occupied by Eu 3+ increased after calcination. Compared to the 5 D 0 → 7 F 1 transition, the higher intensity of the 5 D 0 → 7 F 2 transition was enabled by forced electric dipole [45][46][47][48], which indicated the absence of inversion symmetry around the average Eu 3+ site.…”
Section: Discussionmentioning
confidence: 96%
“…This indicated that the number of sites occupied by Eu 3+ increased after calcination. Compared to the 5 D 0 → 7 F 1 transition, the higher intensity of the 5 D 0 → 7 F 2 transition was enabled by forced electric dipole [45][46][47][48], which indicated the absence of inversion symmetry around the average Eu 3+ site.…”
Section: Discussionmentioning
confidence: 96%
“…The assembly of the MOF proceeds by initial formation of POM-encapsulating cages, which connect in space to for the microporous MOF. Encapsulation of the POM not only enables room temperature synthesis of Cu 3 (BTC) 2 MOF but also protects the structure against degradation in heated, humid conditions (Mustafa et al, 2011) and provides it with cation exchange properties (Bajpe et al, 2013), enabling its conversion into a photoluminescent material by incorporation of rare earth ions and exploiting the metal-organic framework as sensitizer (Mustafa et al, 2014). By adding cetyltrimethylammonium bromide (CTAB) to the synthesis as secondary structure-directing agent, it was discovered that the aggregation sequence of the elemental cages could be altered.…”
Section: Hierarchical Cok-x Metal-organic Frameworkmentioning
confidence: 99%
“…In agreement with the EXAFS results, this clearly rules out the octahedral symmetry commonly observed for the metal sites in LDHs. For noncentrosymmetric crystal fields, the mixing of electronic configurations with opposite parity caused by the odd components of the ligand field partially relaxes the Laporte rule, leading to non-vanishing 4f-4f dipole strengths and increased radiative transition rates 63,64 . Additionally, since the intensity of the (Eu 3+ ) 5 D0→ 7 F1 transition is host-independent, its tabulated radiative transition rate (𝐴 𝑀𝐷 = 14.73 𝑛 3 s -1 ) can used to experimentally determine the total radiative transition probability (A 𝑟𝑎𝑑 ) related to the (Eu 3+ ) 5 D0→ 7 F1,2,4 emissions based on the integral intensities (optical power or spectral irradiance, S1,2,4) and barycentre (λ1,2,4) of the (Eu 3+ ) 5 D0→ 7 F1,2,4 emission bands as:…”
Section: Europium Coordination and Local Environmentmentioning
confidence: 99%